2015
DOI: 10.32350/ibfr.2015.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Islamic House Financing in Pakistan: A Demand Analysis

Abstract: his paper analyzes the issue of the nature of demand for house financing offered by Islamic banks in the Pakistan. The paper also identifies the factors that impact demand for house financing offered by Islamic banks. The study used survey data based on convenient face to face interview of 243 respondents. The study regressed conventional demand for Islamic house financing on six regressors: Shariah compliance, convenience, bank features, product features, social influence and knowledge. The study reveals that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Topic of Study on Islamic Finance for Construction Project are discussed in the articles with issue in end costumer needs which one them is Islamic finance for project must fulfil the client's need such as profitability (Zawawi et al, 2013), one of the paper discussed that Islamic finance for construction has no interest bared (Adelekan et al, 2013) one paper discussed about Islamic project finance opportunity (Javed & Fida, 2015), one paper analysed about Islamic compliant indicator (Osmadi & Zainuddin, 2016) and one paper discussed about comparation between Islamic and conventional financing for project financing (Lone & Quadir, 2017). These papers are generally had approaching discussion on distinguishing the good concept of Islamic project finance, papers that proposed clarification on what is literately basic idea that need to be adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Topic of Study on Islamic Finance for Construction Project are discussed in the articles with issue in end costumer needs which one them is Islamic finance for project must fulfil the client's need such as profitability (Zawawi et al, 2013), one of the paper discussed that Islamic finance for construction has no interest bared (Adelekan et al, 2013) one paper discussed about Islamic project finance opportunity (Javed & Fida, 2015), one paper analysed about Islamic compliant indicator (Osmadi & Zainuddin, 2016) and one paper discussed about comparation between Islamic and conventional financing for project financing (Lone & Quadir, 2017). These papers are generally had approaching discussion on distinguishing the good concept of Islamic project finance, papers that proposed clarification on what is literately basic idea that need to be adopted.…”
Section: Resultsmentioning
confidence: 99%
“…The fulfillment of this obligation brings Divine blessing, which can be defined as an increase in the benefits of the entrusted resources. It infers that compliance to Divine ruling or Shariah compliance increase utility and profitability (Javed & Bukhari et al, 2022) In the context of the objective selected for the current study, the existing literature can be classified into two groups. The first group observes the impact of Shariah compliance on customers' behaviour, and the second examines the effect of Shariah compliance on the financial performance and profitability of Islamic banks as discussed below.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, some studies claimed that Shariah compliance has no impact on the customer behaviour as customers prefer Islamic banks due to some non-religious reasons. For example, Javed et al (2015) analyzed the demand of Islamic house financing in Pakistan and found that majority of the potential customers of Islamic banks are conventional who use Islamic financial services only when they are less expensive regardless of their Shariah compliant status.…”
Section: Impact Of Shariah Compliance On Customers' Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…This study conducted a survey on Dubai residents who were judged to reflect the housing consumers’ recent preferences best. Analytic Hierarchy Process (AHP) was completed to identify the housing determinants and consumers’ preferences for the housing determinants [ 22 , 23 ]. In addition, by using the demographic characteristics of the respondents identified in the survey, preference characteristics by income, place of residence, age, gender, and type of house in which they currently reside were identified [ 24 ].…”
Section: Introductionmentioning
confidence: 99%